The impact of VUS reclassification on reproductive decision making - Alexandra Peyser; Kenan Onel; Avner Hershlag (PLoS ONE, 2025)
Introduction Laboratories will occasionally reclassify a VUS to pathogenic (P) or likely pathogenic (LP), making it clinically actionable. Here, we aim to characterize the frequency of this reclassification in genes tested routinely during preconception counseling in order to help guide reproductive decision making. Design Utilizing the American College of Medical Genetics (ACMG) 113-gene pre-conception panel, we conducted data analysis from ClinVar Miner (https://clinvarminer.genetics.utah.edu/). The numbers of VUS’s reported for each gene were recorded over a 3-year period (2019, 2021, & 2022). In addition, data on the number of VUS’s in conflict (VUS/P and VUS/LP) were recorded. The 10 genes with the most VUS’s and the genes with the most frequent reporting discordance were compared over the 3 years, Results There was a 103% increase in the number of VUS’s reported (2019: 13,278, 2021: 22,434, 2022: 26,965) and a 235% increase in the number of VUS’s in conflict (2019:387, 2021: 946, 2022:1297). The overall percent conflict increased significantly (2019: 2.9% vs. 2022: 4.8%). Nine genes among the top 10 with the most frequent VUS’s remained the same over the 3-year period, while five out of the ten most frequent genes with VUS’s in conflict remained the same. Conclusions The rate of conflicting reporting of a VUS has increased in 3 years and is currently at 4.8%. A potential upgrade of a VUS to pathogenic or likely pathogenic may turn the variant “actionable,” justifying testing embryos for the variant through PGT-M.